A computerized method of quantitative analysis of ventricular phase distributions - Fránquiz, J M; García-Barreto, D; Cárdenas, R (European journal of nuclear medicine, 1983)
Phase images from gated equilibrium cardiac studies, were analysed quantitatively by a computerized automatic method. The study included 17 normal subjects and 33 patients with an acute myocardial infarction (AMI). Phase histograms were constructed for each ventricle and their peaks were identified by a convolution algorithm for smoothing and differentiation. Intra- and interventricular phase shifts as well as the percentage of normal contracting pixels (NCP) were calculated. The results showed that the left ventricular ejection fraction (LVEF) tends to decrease when the intraventricular phase shift increases. Interventricular phase shifts out of the normal range (+/- 10 degrees) were observed predominantly in patients with an extensive anterior or anteroseptal AMI. The closest relationship was found between LVEF and the percentage of NCP. This parameter decreases when akinetic and dyskinetic areas increase and could be considered as a quantitative index of the synchronism in myocardial contraction useful in the prognosis and follow-up of patients.